Penerapan Upacara Bendera dalam Menanamkan Rasa Percaya Diri Anak di TK Muslimat NU Bunga Harapan Lamongan - Rahmania Ainin Permata Rahmania; Ilun Muallifah (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study discusses the implementation of flag ceremonies at Taman Kanak-Kanak Muslimat NU Bunga Harapan Lamongan and its impact on developing children's self-confidence. The flag ceremony is a formal ritual involving the raising of the national flag, conducted regularly in various educational institutions. This research employs a descriptive qualitative approach to depict the phenomena and social interactions within the ceremony activities. Data collection methods include observation, semi-structured interviews, and documentation. The findings indicate that engaging children as alternating officers during flag ceremonies can enhance their self-confidence. Children feel proud and happy when chosen by teachers to perform these roles, contributing to their character development and independence. Therefore, the application of flag ceremonies in educational settings positively influences children's personality formation